2022
DOI: 10.3390/jcm11175073
|View full text |Cite
|
Sign up to set email alerts
|

Potential Usefulness of Blood Urea Nitrogen to Creatinine Ratio in the Prediction and Early Detection of Delirium Motor Subtype in the Intensive Care Unit

Abstract: Prediction and early detection of delirium can improve patient outcomes. A high blood urea nitrogen to creatinine ratio (BCR), which reflects dehydration, has been reported as a risk factor for delirium. Additionally, BCR represents skeletal muscle loss in intensive care unit (ICU) patients, which can have critical implications for clinical outcomes. We investigated whether BCR could be used to predict the occurrence and motor subtype of delirium in ICU patients through a retrospective cohort study that includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Therefore, ICU nurses should pay careful attention to patients' level of consciousness and orient them as necessary. BUN has been identified as a predictor of delirium, and previous studies have reported that acute renal failure increases the risk of delirium ten-fold [45], and that high BUN and creatinine increase the risk of delirium by 1.67 times [46]. Wan et al [47] and Pang et al [48] reported that elevated BUN indicates renal dysfunction and injury, which causes the ineffective elimination of protein metabolites (e.g., uric acid, ammonia) through the kidneys and the consequent accumulation of these wastes in the body.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ICU nurses should pay careful attention to patients' level of consciousness and orient them as necessary. BUN has been identified as a predictor of delirium, and previous studies have reported that acute renal failure increases the risk of delirium ten-fold [45], and that high BUN and creatinine increase the risk of delirium by 1.67 times [46]. Wan et al [47] and Pang et al [48] reported that elevated BUN indicates renal dysfunction and injury, which causes the ineffective elimination of protein metabolites (e.g., uric acid, ammonia) through the kidneys and the consequent accumulation of these wastes in the body.…”
Section: Discussionmentioning
confidence: 99%
“… 46 47 One recent study reported an association between increased BUN and occurrence of hypoactive delirium. 28 Increased BUN, sodium, and pH may reflect a dehydrated state. Research has demonstrated that a state of dehydration may contribute to the occurrence of delirium through the mechanisms of cerebral hypoperfusion and modification of neurotransmitter levels in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…These clinical variables are known to be associated with delirium and are present in the majority of patients. These included laboratory values, vital signs, and information about devices used during the hospitalization assessment [laboratory test results: blood urea nitrogen (BUN), 28 pH, 29 bicarbonate, 29 C-reactive protein, 30 albumin, 31 total bilirubin, 31 sodium, 32 hemoglobin, 33 hematocrit 33 ; vital signs: 34 temperature, diastolic blood pressure, systolic blood pressure, heart rate, and respiratory rate; information about used devices: 34 vascular catheter, urinary catheter, neurosurgical drainage tube, restraints, and mechanical ventilator]. Missing values for categorical variables were assigned to their own null category.…”
Section: Methodsmentioning
confidence: 99%